2021
DOI: 10.2741/4915
|View full text |Cite
|
Sign up to set email alerts
|

MTiness in pseudo-malignant behavior of trophoblasts during embryo implantation

Abstract: EMT during trophoblast invasion factor SC35, etc. to be essential for early implantation. Trophoblasts, that form the outer epithelial layer of the blastocyst, participate in the formation of the placenta. During placentation, invasive extravillous trophoblasts (EVTs), migrate into the endometrium, and a transient epithelial to mesenchymal transition (EMT) and remodel the uterine arteries for blood and nutrient exchange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…We have shown that TGF-β1 inhibits human EVT cell invasion by inducing Snail-mediated down-regulation of the expression of vascular endothelial-cadherin (VE-cadherin) [ 9 ]. Notably, EMT has now been considered an important process that regulates EVT cell invasion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that TGF-β1 inhibits human EVT cell invasion by inducing Snail-mediated down-regulation of the expression of vascular endothelial-cadherin (VE-cadherin) [ 9 ]. Notably, EMT has now been considered an important process that regulates EVT cell invasion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This involves the exchange of nutrients and waste materials across the feto-placental unit. Trophoblast cells are transiently invasive [ 35 , 36 ] and participate in the remodeling of the maternal uterine matrix and its vasculature to gain access to its nutrient-rich milieu. Successful pregnancy depends on the efficiency of this process, which depends on an efficient trophoblast differentiation program.…”
Section: Introductionmentioning
confidence: 99%
“…This also involves the exchange of nutrients and waste across the feto-placental unit. Trophoblast cells are pseudo-malignant 28 and transiently invasive 29 , participating in remodeling the maternal uterine matrix and its vasculature to gain access to its nutrient-rich milieu. Successful pregnancy depends on how e ciently this process is accomplished.…”
Section: Introductionmentioning
confidence: 99%